(untitled) (Malaysian Journal of Learning and Instruction, 2006)
This paper aims to discuss teachers’ degree of implementation of the KBSM (Revised) English Language Curriculum, introduced in 2003. It also sets to highlight the inhibiting factors that had impeded teachers’ implementation of the Skills Specifications or activities suggested in the Huraian Sukatan Pelajaran (HSP) Bahasa Inggeris Tingkatan Empat of the new curriculum. Firstly, the author finds that about 60 percent of the teachers obtained only a medium degree of implementation for 18 out of the 22 Skills Specifications. Secondly, the author concludes that among the prominent factors that had inhibited teachers’ implementation of the KBSM (Revised) English language curriculum in Malaysian classrooms were too many components of the new curriculum, hence leading to lack of understanding of the curriculum, lack of in-service training, time constraints and finally inadequate and irrelevant teaching materials.